Health promotion and health risks in school everyday life: Experienced paradoxes about middle school pupils' health and the role of school health services among pupils, teachers and school managers - Søfteland, Marta Olsen; Thørrisen, Mikkel Magnus; Aas, Randi Wågø (Nordisk Tidsskrift for Helseforskning, 2024)
The objective of this study was to provide an increased understanding of health challenges among pupils and the roles of schools and school health services. This was done from the perspectives of pupils, teachers and school managers. Four focus group interviews with middle school pupils, teachers and school managers (N = 26) were conducted at one large school in Southern Norway. Data were analyzed using qualitative content analysis. Three themes and nine sub-themes were identified, uncovering two paradoxes: (i) pupils’ health challenges were perceived as complex, while the school health services were not interdisciplinary and were scarcely accessible, and (ii) the school environment was experienced as an arena having an impact on pupils’ health, but there was a lack of health competence in the school (among pupils, teachers and management). The study suggests that schools have potential to be a health-promoting environment, and that co-creation processes involving pupils, teachers, managers and an interdisciplinary school health services team could contribute to a more autonomy-supportive, prosocial, and health-promoting school environment.
Keywords: Health-promoting schools; school health services; interdisciplinary; middle school pupils; teachers; school managers